Frequency distribution of virulence factors in uropathogenic Escherichia coli isolated from Kermanshah in 2011-2012 - Mohajeri, Parviz (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Uropathogenic Escherichia coli (UPEC) can cause urinary tract infection (UTI). To prevent urine flow lavage, UPEC has acquired several virulence factors called adhesins. These adhesins are expressed and controlled by different genes. AIM: This study was aimed to determine some of the most important genes that control virulence factors of UPEC (pyelonephritis associated pili [pap], S fimbrial adhesion [sfa] and A fimbrial adhesion [afa] genes), which code for adhesins and phenotypic factors. MATERIALS AND METHODS: In total, 205 UPEC isolates from in- and out-patients with UTI were obtained. Polymerase chain reaction was used for gene amplification. One drop of bacterial suspension, one of red blood cells and one of peripheral blood smear were mixed for hemagglutination (HA). Formation of a clump was considered to be positive. Bacteria were grown on blood agar to determine hemolysis. Surface hydrophobicity was determined using the SAT test. RESULT: Frequencies of pap, afa and sfa were 42 (20.5%), 17 (8.3%) and 44 (21.5%), respectively. Frequencies of HA, hemolysis and hydrophobicity were 138 (67.3%), 56 (27.3%) and 39 (19%), respectively. Among HA-positive bacteria, 103 (74.6%) were mannose resistant. Our results highlight higher frequency of HA than that of other virulence factors, indicating a crucial role of this virulence factor in UPEC. DISCUSSION: We concluded that major differences exist in the prevalence of virulence factors among different UPEC isolated from different countries. The association observed between pathogenicity and virulence factors may promote UPEC survival and growth within the urinary tract. Detecting these genes as the primary controllers of UPEC virulence factors may aid in better management of related infections.